Penerapan Permainan Tradisional Congklak untuk Mengembangkan Kemampuan Konsep Berhitung Pemula dan Motorik Halus Anak Usia 4-5 Tahun di TK Hati Suci Jakarta [Application of the Traditional Congklak Game to Develop Beginner Numeracy Skills and Fine Motor Skills in Children Aged 4-5 Years at Hati Suci Kindergarten, Jakarta] - Rahmat, Tiara Juliana (Jurnal Teropong Pendidikan, 2022)
This research was conducted to develop the ability of beginner numeracy skills and fine motor skills of 4-5 year children by implementing the traditional Congklak game, which aims to describe the ability of beginner numeracy concepts and fine motor skills of children aged 4-5 years after the implementation of traditional Congklak game. The method used in this research is classroom action research which is carried out in three cycles with 2 actions in each cycle. The results obtained were the children's beginner's numeracy ability on indicator 1 increased in cycle III to 33.75%. In indicator 2, it increases in cycle III to 45.00%. In indicator 3, it increases in cycle III to 38.75%. And the percentage results on the assessment of children's fine motor skills on indicators increased in cycle III to 18.75%. In indicator 2 it increases to 38.75%. In indicator 3 it increases to 28.75%. It can be concluded that the application of traditional Congklak game can develop beginner numeracy skills and fine motor skills in children aged 4-5 years.